Aldosterone receptor blockers spironolactone and canrenone: two multivalent drugs. (May 2014) - Armanini, Decio; Sabbadin, Chiara; Donà, Gabriella; Clari, Giulio; Bordin, Luciana
<x xml:space="preserve">Abstract</x> Canrenone is a derivative of spironolactone with lower antiandrogen activity. The drug is used only in few countries and can block all the side effects of aldosterone (ALDO). The drug is effective even in the presence of normal concentrations of ALDO. Mineralcorticoid receptor antagonists block the inflammatory activity of ALDO at the level of target tissues as heart, vessels and mononuclear leukocytes. Canrenone reduces the progression of insulin resistance and of microalbuminuria in type 2 diabetes and other related diseases. Both canrenone and hydrochlorothiazide can enhance the effect of treatment with ACE inhibitors and angiotensin II receptor blockers on microalbuminuria, but ALDO receptor blockers are more active. This different action is due to the fact that only canrenone blocks mineralocorticoid receptors. Serum potassium and renal function should be monitored before and during the treatment. ALDO receptor blockers are recommended in addition to polytherapy for resistant hypertension, but there are no studies on the effect of the drug as first-choice therapy.